Effects of Aleurone Supplementation on Glucose-Insulin Metabolism and Gut Microbiome in Untrained Healthy Horses - Boshuizen, Berit; Moreno de Vega, Carmen Vidal; De Maré, Lorie; de Meeûs, Constance; de Oliveira, Jean Eduardo; Hosotani, Guilherme; Gansemans, Yannick; Deforce, Dieter; Van Nieuwerburgh, Filip; Delesalle, Catherine (Frontiers in Veterinary Science, 2021)
Aleurone is the layer within the bran fraction, deemed to be responsible for the positive health effects associated with the consumption of whole-grain products. Studies in rodents, pigs, and humans report beneficial effects in five main areas: reduction of oxidative stress, immunomodulatory effects, modulation of energy management, digestive health, vitamin and mineral storage. This is the first aleurone supplementation study performed in horses. The aim of the study was to investigate the effect of increasing doses of aleurone on postprandial glucose-insulin metabolism and the fecal microbiome in healthy untrained horses. Seven adult Standardbred horses were supplemented with four different aleurone doses (50, 100, 200, 400 g/day during 1 week), using a Latin Square model with 1 week wash-out in between doses. On day 7 of each supplementation week, postprandial blood glucose-insulin was measured and fecal samples were collected. 16S rRNA gene sequencing was performed and QIIME2 software was used for microbiome analysis. Microbial community function was assessed using the predictive metagenome analysis tool PICRUSt using the Metacyc metabolic pathways database. Relative pathway abundancies were analyzed using ANCOM in R. There was a significant dose-dependent increase in the postprandial time to peak of glucose (p=0.030) and a significant delay in time to peak of insulin (p=0.025) and a significant decrease in both insulin peak level (p=0.049) and insulin AUC (p=0.019) with increasing aleurone doses, with 200 g being the lowest significant dose. Alpha- and beta diversity of the fecal microbiome showed no significant changes. Aleurone significantly decreased the relative abundance of the genera Roseburia, Shuttleworthia, Anaerostipes, Faecalibacter and Succinovibrionaceae. The most pronounced changes in relative abundance at phyla level were seen in Firmicutes and Verrucomicrobia (down-regulation) and Bacteroidetes and Spirochaetes (upregulation). PICRUSt analysis shows that aleurone induces a downregulation of L-glutamate and taurine degradation and upregulation of three consecutive pathways of phospholipid membrane synthesis of the Archaea domain. The results of this study suggest a multimodal effect of aleurone on glucose-insulin metabolism, most likely caused by the effect on feed texture and subsequent digestive processing; the synergistic effect of individual aleurone components on glucose-insulin metabolism and on microbiome composition and function.